1974
DOI: 10.1111/j.1432-1033.1974.tb03693.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Kinetic Properties of α, β and Ψ Forms of Trypsin

Abstract: The kinetics of ester substrate hydrolysis catalysed by the a, j, and $ forms of trypsin have been compared. An affinity chromatography method for +-trypsin purification is described. At optimum pH, with esters as substrates, there is no significant difference between the activity of the a and j forms; j-trypsin, however, is about 40 % more active than a-trypsin on benzoyl-L-arginine amide.At acidic pH, (= 3.6), j3-trypsin is more reactive toward p-nitrophenyl-p'-guanidino benzoate HCl than a-trypsin, and diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 33 publications
3
21
0
Order By: Relevance
“…Determination of specific activities of commercial and purified trypsin isoforms was made using BApNA (Erlanger, et al, 1961), and the results are shown in fig.4. The results are in accordance to Foucault (Foulcault, et al, 1974a andFoulcault, et al, 1974b). The low specific activity found with commercial trypsin is due to factors unstabilizing the sample, as peptides inhibitors in the commercial trypsin preparation, storage time or storage at very low temperatures, possibly leading to cold denaturation.…”
Section: Reproducibility Testsupporting
confidence: 87%
“…Determination of specific activities of commercial and purified trypsin isoforms was made using BApNA (Erlanger, et al, 1961), and the results are shown in fig.4. The results are in accordance to Foucault (Foulcault, et al, 1974a andFoulcault, et al, 1974b). The low specific activity found with commercial trypsin is due to factors unstabilizing the sample, as peptides inhibitors in the commercial trypsin preparation, storage time or storage at very low temperatures, possibly leading to cold denaturation.…”
Section: Reproducibility Testsupporting
confidence: 87%
“…Although the D. hansenii UFV-1 extracellular and intracellular ␣-galactosidases had presented similar properties, as molecular mass (by MALDI-TOF and SDS-PAGE), N-terminal amino acid sequences [16], and secondary structures, thermodynamic and kinetic significant differences showed that the ␣-galactosidases (extra-and intracellular) exist as two isoforms. Similar results were found for other well studied proteins, such as the trypsin isoforms [37,38].…”
Section: Thermal Denaturationsupporting
confidence: 87%
“…Thus, the calorimetric analysis supply more reliable thermodynamic data, therefore the calorimetric measured is resultant of direct thermal effects of protein denaturation. This data complement the spectroscopic structural studies, supplying a more complete description of the system (protein + carbohydrate + solvent) [20,38].…”
Section: Thermal Denaturationmentioning
confidence: 99%
“…Trypsin activity was assayed using BAEE as described by Schwert and Takenaka (1955). The method of Foucault et al (1974) with BAA and BAEE was used to discriminate the a and b forms of trypsin. Subtilisin activity was followed using TAME as described by Rick (1974).…”
Section: Protein and Enzymatic Activity Assaysmentioning
confidence: 99%